1_ (2-7) : (-5) -2 . (-2)=

2_ -3.9-7 (-3) + 4 . ( -8)=

3_ (4+8): ( -1) +3=

4_ -3.(-8) +5 -4 +3 =

5_ -3 . (-8) - (-4) - 4 =

6_ -2. (-1) + 3.0 -3 . (-2)=

7_ (4-9): (-5) + (-8) . 7 +4 =

8_ (-8+9).7 +2 . (-5) + 3=

9_-49: (-7) + (-45+2). (-2)=

graciias respondan ypaso por paso. :$

2

Respuestas

2013-03-29T05:42:44+01:00

1. (2-7) : (-5)-2(-2) = -5 : -5+4 = 1+4 = 5
2.  -3.9-7 (-3) + 4 . ( -8) = -18-7-3+4 = -25+1 = -24
3.   (4+8): ( -1) +3 = 12 : -1+3 = -12 +3 = -9
4.  -3.(-8) +5 -4 +3 = 24 +4 = 28
5.  -3 . (-8) - (-4) - 4 = 24 +4-4 = 24
6.  
-2. (-1) + 3.0 -3 . (-2) = 2+6 = 8
7.  
(4-9): (-5) + (-8) . 7 +4 = 1+(-56)+4 = -51
8.  
 (-8+9).7 +2 . (-5) + 3 = 7+(-10)+3 = 0
9.  
-49: (-7) + (-45+2). (-2) = 7+(-43).(-2) = 7+86 = 93

2013-03-29T10:59:36+01:00

 (2-7) : (-5)-2(-2) = -5 : -5+4 = 1+4 = 5
  -3.9-7 (-3) + 4 . ( -8) = -18-7-3+4 = -25+1 = -24
  (4+8): ( -1) +3 = 12 : -1+3 = -12 +3 = -9
  -3.(-8) +5 -4 +3 = 24 +4 = 28
  -3 . (-8) - (-4) - 4 = 24 +4-4 = 24
 
-2. (-1) + 3.0 -3 . (-2) = 2+6 = 8
  
(4-9): (-5) + (-8) . 7 +4 = 1+(-56)+4 = -51
  
 (-8+9).7 +2 . (-5) + 3 = 7+(-10)+3 = 0
  
-49: (-7) + (-45+2). (-2) = 7+(-43).(-2) = 7+86 = 93